1999
DOI: 10.1523/jneurosci.19-23-10397.1999
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Tuning in a Spinal Nociceptive System: Effects of Neonatal Spinalization

Abstract: Recent studies indicate a modular organization of the nociceptive withdrawal reflex system. Each module has a characteristic receptive field, closely matching the withdrawal movement caused by its effector muscle. In the rat, the strength of the sensory input to each module is tuned during the first postnatal weeks, i.e., erroneous spinal connections are depressed, and adequate connections are strengthened. To clarify if this tuning is dependent on supraspinal structures, the effect of a complete neonatal spin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
35
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(36 citation statements)
references
References 37 publications
1
35
0
Order By: Relevance
“…Sensory feedback from spontaneous movements expressed during the newborn period has been shown to be necessary for the correct development of this reflex (Petersson et al, 2003 Waldenström, Thelin, Thimansson, Levinsson, & Schouenborg, 2003). Although the spinal cord can generate spontaneous twitches and eventually houses the withdrawal reflex circuitry, a neonatal spinal transection leads to aberrant responses and the reflex circuit does not develop properly (Levinsson, Luo, Holmberg, & Schouenborg, 1999). Therefore, proper development and fine-tuning of the nociceptive withdrawal reflex is the product of spinal activity, sensory feedback from spontaneous movements, and supraspinal regulation of spinal mechanisms.…”
Section: Developmental Mechanisms Of Motor Plasticitymentioning
confidence: 99%
“…Sensory feedback from spontaneous movements expressed during the newborn period has been shown to be necessary for the correct development of this reflex (Petersson et al, 2003 Waldenström, Thelin, Thimansson, Levinsson, & Schouenborg, 2003). Although the spinal cord can generate spontaneous twitches and eventually houses the withdrawal reflex circuitry, a neonatal spinal transection leads to aberrant responses and the reflex circuit does not develop properly (Levinsson, Luo, Holmberg, & Schouenborg, 1999). Therefore, proper development and fine-tuning of the nociceptive withdrawal reflex is the product of spinal activity, sensory feedback from spontaneous movements, and supraspinal regulation of spinal mechanisms.…”
Section: Developmental Mechanisms Of Motor Plasticitymentioning
confidence: 99%
“…Nevertheless, numerous anatomical and electrophysiological studies in rat pups have shown that the properties of nociceptive reflexes and their underlying dorsal horn nociceptive circuits differ in early postnatal life from those in adults [12], [16][18]. Most notably, withdrawal reflexes in rat pups have lower thresholds, in the innocuous range, and are greater in amplitude and duration than adult rats and the underlying dorsal horn neurons and reflex motoneurones have larger, disorganised cutaneous receptive fields [16], [19][22]. The changing properties of newborn rodent reflexes are due, at least in part, to the postnatal development of spinal sensory circuits.…”
Section: Introductionmentioning
confidence: 99%
“…The spinal cord, like the rest of the CNS, undergoes activitydependent plasticity in development, during skill acquisition, and in response to trauma and disease (Goode and Van Hoven, 1982;Myklebust et al, 1982Myklebust et al, , 1986Casabona et al, 1990;Koceja et al, 1991;O'Sullivan et al, 1991;Nielsen et al, 1993;Straka and Dieringer, 1995;Levinsson et al, 1999;Wolpaw and Tennissen, 2001) (for review, see . The activity that induces spinal cord plasticity comes from peripheral sensory receptors via dorsal root input pathways and from the brain via descending pathways.…”
Section: Introductionmentioning
confidence: 99%